IDENTIFIKASI DAN PENTAHAPAN ZONA AKTIFITAS WISATA PANTAI SELATAN DIY - Prakoso, Aditha Agung (Universitas Aisyiyah Yogyakarta, 2018)
Southern area of Yogyakarta Special Region is a row of beaches that become a natural tourist attraction for tourists who visit. This beach area stretches from Kulon Progo Regency in the West to Gunungkidul Regency in the East.The visits of tourists in the area, providing changes to local activities that previously existed. This resulted in a variety of potential development activities and interaction patterns that appear in each of its beaches.The changes and developments will be mapped and overlaid to find the development of zone activity on the South Coast of Yogyakarta Special Region. This research will be focused on several beaches in Kulon Progo, Bantul and Gunungkidul regencies.And later this research will be useful for the Government of Yogyakarta, Specifically for Kulon Progo, Bantul and Gunungkidul regencies to develop tourism development policy in South Area of Yogyakarta Special Region.